Sosialisasi & Inventarisasi Potensi Desa Wisata di Desa Cikalong Kecamatan Cimaung Kabupaten Bandung - Reza Martani Surdia; Apriadi Budi Raharja; Budi Heri Pirngadie; Supratignyo Aji (LPPM UNINUS, 2019)
Palasari Village, Cikalong Village has the potential of the agricultural and plantation sectors, this is illustrated by the population structure of the Cikalong Village based on the type of livelihood of the people who also use the land distributed. It is unfortunate that the potential of agriculture isn’t seen from other perspectives as a tourist attraction.